A novel, combined reflector antenna design procedure for ultra-wide band planar lens antenna feeds - Sonmez, Nurdan; Tokan, Fikret (ELSEVIER GMBH, 2021)
Feeding structure in a reflector system directly affects radiation characteristics of the antenna. With this research, a design procedure is introduced for high gain reflectors with ultra-wide band (UWB) planar dielectric lens antenna (PDLA) feeds. Traditionally, feed elements for broadband reflector applications require to exhibit frequency stable radiation patterns and phase center positions across a broad frequency band. However, UWB PDLAs have highly directive radiations in one plane and broad fan beams on the other plane. Phase center of a PDLA is almost stable in one plane, whereas apparent phase center variation is observed in the other plane. The phase center in the latter plane is located far behind the antenna and moves significantly with frequency. Although PDLAs have these unfavorable radiation characteristics as reflector feeds, using the introduced, novel procedure, highly directive radiation is achieved in 4-9 GHz frequency band. The illuminated reflector is designed by combining two parabolic reflectors having different and appropriate focal length-to-diameter (F/D) ratios to favor E- and H-plane feed radiations. Simulated results are validated by both ray tracing method and analytic solutions.
Keywords: Lateral wave antenna; Parabolic reflector; Phase center; Planar dielectric lens antenna; INTEGRATED LENS; HORN; SIMULATION; Engineering; Telecommunications